FRI0502 Osteoporosis and Fracture Risk in Outpatients with Systemic Sclerosis. (10th June 2014) - Breda, S.; Inverardi, F.; Codullo, V.; Bogliolo, L.; De Nard, F.; Cagnotto, G.; Caporali, R.; Montecucco, C.
Abstract : Background: Osteoporosis (OP) is a frequent complication of a number of chronic inflammatory diseases. Only Rheumatoid Arthritis (RA) is included in the FRAX algorythm to calculate fracture risk but also Systemic Sclerosis (SSc) displays many disease-specific OP risk factors (chronic inflammation, malnutrition, steroid use, etc.) Objectives: To determine OP frequency and fracture risk by FRAX in outpatients with SSc Methods: After consent, in outpatients with SSc (le Roy criteria) of a University Hospital, bone mineral density (BMD) was calculated by Dual Energy X-Ray Absorptiometry (DEXA) at the femoral neck and lumbar spine and FRAX was obtained by the calculation tool (http://www.shef.ac.uk/FRAX ). A routine SSc evaluation (according to EUSTAR) was performed as well. Age- and BMI-matched early AR (ACR/EULAR 2010 criteria) patients and healthy controls (HC) were enrolled as well. Results: Seventy-one SSc patients (3:68 M:F, age 66±9yrs, 57:14 limited:diffuse cutaneous, median disease duration 8.5, 2.4-14.7yrs, median disease activity 1, 0.25-2), 44 AR (11:33 M:F, age 62±12yrs, median DAS28 4.42, 3.94-5) and 29 healthy controls (all F, 60.1±10.7yrs) were enrolled. OP was detected in 42/71 (59%) SSc patients. Disease duration was significantly higher in SSc-OP patients (10.5, 4.3-16.6 vs 5.5, 1.6-9.8, p<0.01) and it was also significantly associated to OP (OR 1.4, 1.1-1.7, p<0.01), even when corrected at a multivariable analysis for other disease-specific features (skin and gastrointestinal involvement, autoantibody subset, median mRSS, disease activity) and OP risk factors (steroid use, smoke, BMI, chronic renal insufficiency). OP in RA patients was significantly lower than in SSc (9/44, 20%, p<0.001). Mean femoral BMD was 0.58 (0.53-0.7) in SSc vs 0.72 (0.64-0.82) in RA and 0.7 (0.51-0.75) in HC (p<0.0001), lumbar mean BMD 0.82 (0.75-0.9) in SSc vs 0.92 (0.81-1) in RA and 0.89 (0.67-0.99) in hc (p=NS). FRAX for major fracture was not significantly different between disease groups (low in 47% and 50%, medium in 28% and 40%, high in 25% and 10% of SSc and RA respectively) while it was significantly different for SSc vs HC (p<0.001) and for AR vs HC (p<0.01). A diagnosis of SSc was significantly associated to OP (OR=13.2, 4-42.4), even when corrected for steroid use. Conclusions: We have detected a very high OP frequency in our SSc patients, significantly higher than a control early AR cohort and significantly associated to disease duration. Routine DEXA evaluation and risk factors for OP should always be considered and treated when possible in every SSc patient, especially after 5 years of disease duration. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5172